Synphytosozological investigation of vegetation of the island Dzharylgach (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
Clarified syntaxonomical structure of sozological of communities halo nitrophylous (Cakiletea maritimae), psamophytic (Ammophiletea) and psamophytic steppe (Festucetea vaginatae) vegetation of Dzharylgach island is given. They are represented by six associations and one basal community that belong to three unions, three orders and three classes. There is a classification scheme, phytocenotic and synoptic tables, given characteristics within the classes and associations, assessed degree of rarity by sozological features of diagnostic species. New for the island syntaxons, class Cakiletea maritimae, associations Lactuco tataricae-Cakiletum euxinae, Tournefortietum sibiricae and community Trachomitum venetum subsp. russanovii were found.
Keywords: syntaxonomy, vegetation, sozophyites, National Park «Dzharylgachsky».